(untitled) (Scientific journal of the Fergana State University, 2023)
This article describes the history of the study of the thematic group of household vocabulary dishes and kitchen utensils in English and Uzbek linguistics, and explains with examples the study of lexemes in this category in specific areas. The importance of a comprehensive study of lexical units in linguistics, their in-depth study of the language system and the internal relations between the words that make up separate lexical-semantic groups, the etymology, construction, synchronous and diachronic status of language units The study of structural-semantic, linguocultural and linguocognitive research on the example of specific languages, the achievement of a number of scientific results, the analysis of scientific works of Uzbek and English linguists in this field, the study of their different perspectives. The research focuses on the occurrence and meaning of each lexical unit analyzed in the historical sources of the language, as well as variants of the name in the dialects of Turkic languages ​​in the object, phraseological expressions formed with the participation of industry-specific names, onomastic cases. The etymology of nouns, their naming methods, phonetic, lexical-semantic and grammatical features, as well as morphological and syntactic words and phrases are described in detail in the work.